Numerical modelling based assessment of setting load requirement for optimum performance of powered roof supports in longwall workings - Singh G.S.P.; Singh U.K. (My University, 2025)
The influence of setting load for effective strata control at a longwall face is highly debated. Field observations conducted by researchers worldwide suggest a large range of setting load variation from 30 to 80% of yield load of support. The exact quantification of optimum setting load for given strata condition has not been possible with the existing methodologies. This paper describes the results of a numerical modelling study to assess the optimum setting load requirement in longwall workings. The study suggests that the criteria for selection of the optimal setting load should be based on peak roof convergence at the face so that there is no significant deterioration of roof causing any practical difficulty in smooth face advance during periodic weighting at the face. This is a prerequisite condition for maintaining an efficient strata control during progressive face advance for safety and sustainability of the longwall face operation. © 2009 Institute of Materials, Minerals and Mining.